Outcomes from treatment of Granulomatous lobular mastitis - Yuliya B. Olimpiadi (Elsevier, 2021)
Background: Granulomatous lobular mastitis (GLM) is an uncommon benign breast condition characterized by non-caseating Granulomatous inflammation arising from the lobules of the breast. Current therapeutic options include observation, percutaneous aspiration, antibiotics, steroids, methotrexate, and surgical procedures. This study evaluated the effectiveness of therapeutic modalities on the duration of disease and recurrence rate. Study design: A retrospective analysis was performed of clinical, radiographic, and therapeutic data for patients presenting with GLM from January 2008 until October 2018. All patients had a core breast biopsy demonstrating granulomas. Patients with other known sources of granulomas were identified. The use of observation, steroids, methotrexate, abscess aspiration, and surgical procedures was evaluated. Results: There were 285 female patients, predominantly Hispanic (n = 265, 93%) with mean age of 35.6 ± 8.7 years at time of diagnosis. The majority of patients (n = 213, 75%) presented with a mass, mean size 4.2 ± 2.5 cm. Twelve (4%) patients had coexisting autoimmune diseases. Antibiotics were utilized in 217 (76%) patients for courses that averaged 3.4 ± 2.2 weeks. Glucocorticoids were used in 80 (28%) patients, and methotrexate was used in 16 (5%). Incision and drainage or surgical excision was performed for 76 (27%) of patients. The median duration of disease was 16 (IQR: 7–33) weeks and the overall recurrence rate was 22%. Both duration of disease and recurrence rate were highest amongst patients treated with a surgical intervention. Conclusions: The self-limited course of disease and relatively low recurrence rate, in addition to longer disease duration and increased recurrence rate noted in patients treated with incision and drainage and/or surgical excision, appears to justify the infrequent use of surgical procedures in the management of GLM.